The Greenhouse Effect and High-Moisture Coals - Guang LX; Fernando N (The Australasian Institute of Mining and Metallurgy, 1989)
Brown coal in Victoria in spite of its substantial reserves is not utilized greatly because of its high moisture content(-65% w/w). Transportation and handling costs of raw brown coal, on an available energy basis are so expensive that 93% of production is burnt for electricity generation on or adjacent to the coal deposit in Victoria. With direct firing of moist brown coal in power stations, approximately 20% of the gross calorific value of the fuse is used to evaporate the water contained in the coal. This energy is lost as vapour with the flue gas which is vented to the atmosphere. Also there is a 25% increase in flue gas volume and the size and cost of most of the units through which it passes must be appropriately larger. Since there are large quantities of water present the flame temperature is significantly reduced. For zero excess air and no air pre-heating the theoretical flame temperatures are: 609'o wow moisture 1450¦C 40% ª ª ª 1790¦C ZOO ª ª ª 1990¦C As a result of this there is a reduction in radiant heat transfer leading to a requirement for a two fold increase in radiant tube area. A boiler of much greater size and cost is thus required to house the additional tubes. Figure 1 illustrates the relative sizes of a boiler fired with 60% moisture brown coal with a boiler or similar output fed with a British bituminous coal, 14% moisture.